Arginine side-chain modification that occurs during copper-catalysed azide–alkyne click reactions resembles an advanced glycation end product. Issue 26 (10th June 2016) - Conibear, Anne C.; Farbiarz, Karine; Mayer, Rupert L.; Matveenko, Maria; Kählig, Hanspeter; Becker, Christian F. W.
Abstract : An adduct of dehydroascorbate with arginine forms during copper-catalysed azide–alkyne click reactions and resembles an advanced glycation end product. Abstract : Dehydroascorbate is a by-product of copper-catalysed azide–alkyne click (CuAAC) reactions and also forms advanced glycation end products (AGEs) in tissues undergoing oxidative stress. Here we isolate and characterize an arginine–dehydroascorbate adduct formed during CuAAC reactions, investigate strategies for preventing its formation, and propose its biological relevance as an AGE.